Low-emissivity coated glass and processing technology thereof
By adopting a combined structure of plasma-modified silver layer, ZIF-8/polyacrylic hybrid protective layer and hydrophobic antioxidant layer in low-radiation coating glass, the problem of silver layer oxidation is solved, and higher antioxidant performance and long-term stability are achieved.
Patent Information
- Application Number
- CN202510165303.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The silver layer in low-radiation coating glass is easy to react with oxygen and water vapor, resulting in oxidation and degradation of performance. How to effectively prevent the oxidation of the silver layer and improve the long-term stability of the film layer is an urgent problem.
The combined structure of plasma-modified silver layer, ZIF-8/polyacrylic hybrid protective layer and hydrophobic antioxidant layer is adopted, and the silver layer is modified by plasma mixed gas to form a silver fluoride layer. The pore structure of ZIF-8 and the adhesion of polyacrylic acid are used to enhance the antioxidant performance by combining the multiple protection mechanisms of fluorine-containing hyperbranched polymer and nano cerium oxide.
Effectively isolate the direct contact between oxygen and water vapor and the silver layer, slow down the oxidation process of the silver layer, and significantly improve the oxidation resistance and overall performance of low-radiation glass.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coated glass, and in particular to a low-radiative coated glass and a processing technology thereof. Background Art
[0002] Low-E coated glass, also known as Low-E glass, is a special glass material. It is made by coating the glass surface with multiple layers of metal or metal compound films. These films have low-emissivity characteristics and can effectively reduce the emissivity of the glass surface, thereby achieving energy-saving effects. Low-E coated glass has a high transmittance to visible light and can efficiently reflect mid- and far-infrared rays. It can block outdoor heat from entering the room in summer and reduce indoor heat loss in winter, thereby reducing the energy consumption of air conditioning and heating. Therefore, low-E coated glass is widely used in building curtain walls, doors and windows, etc., to improve the thermal insulation performance of buildings and reduce energy consumption. Among them, since silver has low emissivity and high transmittance, a silver layer is often coated on low-E coated glass. However, the silver layer easily reacts with oxygen and water vapor, resulting in oxidation and performance degradation. How to effectively prevent the oxidation of the silver layer and improve the long-term stability of the film layer is an urgent problem to be solved. Summary of the invention
[0003] In view of this, the present invention proposes a low-emissivity coated glass and a processing technology thereof to solve the above problems.
[0004] The technical solution of the present invention is achieved in this way:
[0005] A low-radiation coated glass comprises a glass substrate and an adhesion promoting layer, a plasma modified silver layer, a ZIF-8 / polyacrylic acid hybrid protective layer and a hydrophobic anti-oxidation layer which are sequentially arranged on the glass substrate.
[0006] Furthermore, the thickness of the adhesion promotion layer is 50-150 nm, the thickness of the plasma modified silver layer is 20-50 nm, the thickness of the ZIF-8 / polyacrylic acid hybrid protective layer is 100-200 nm, and the thickness of the hydrophobic anti-oxidation layer is 50-100 nm.
[0007] Furthermore, the raw materials of the adhesion promotion layer are composed of polyether modified silicone oil, acrylic resin, nano titanium dioxide and isocyanate in a mass volume ratio of g / mL of (1-3):(3-5):(0.2-0.6):(0.5-1.0).
[0008] Furthermore, the ZIF-8 / polyacrylic acid hybrid protective layer raw materials are composed of ZIF-8, polyacrylic acid, sodium hexametaphosphate, fluorocarbon leveling agent, and deionized water in a mass volume ratio of g / mL of (3-5):(4-8):(0.2-0.5):(0.1-0.3):(20-40).
[0009] Furthermore, the raw materials of the hydrophobic antioxidant layer are composed of fluorine-containing hyperbranched polymer, nano cerium oxide, organic-inorganic hybrid silicone resin, hindered amine light stabilizer Tinuvin 770, and isopropyl alcohol with a mass volume ratio of g / mL of (2-4):(1-3):(2-4):(0.5-1.5):(20-30).
[0010] Further, the fluorine-containing hyperbranched polymer is prepared by the following method: perfluorooctyl ethyl acrylate, benzoyl peroxide, and dodecyl mercaptan are added to tetrahydrofuran, and stirred at 200-400r / min for 30-60min to obtain a reaction mixture. The mass volume ratio of perfluorooctyl ethyl acrylate, benzoyl peroxide, dodecyl mercaptan, and tetrahydrofuran is (5-7) g / mL: (0.1-0.3): (0.05-0.2): (2-4). Under a nitrogen atmosphere, the reaction mixture is heated to 60-80° C. for reaction, and the stirring is maintained at 200-400r / min during the reaction, and the reaction is reacted for 6-10h to obtain a reaction product. The reaction product is cooled to room temperature, and then placed in a vacuum distillation apparatus, and distilled under the conditions of a vacuum degree of 30-50mba and a temperature of 40-50°C, and the distillation is stopped when the solvent in the receiving bottle no longer increases to obtain a solid substance, and the solid substance is washed 2-3 times with ethanol, and then the solid substance is placed in a drying oven at 40-60°C for 12-20h to obtain a fluorine-containing hyperbranched polymer.
[0011] Further, the organic-inorganic hybrid silicone resin is prepared by the following method: methyl triethoxysilane and polyethylene glycol are added to ethanol, stirred at 100-300 r / min for 10-30 min, and then hydrochloric acid is added under stirring conditions of 200-300 r / min, and reacted at 50-70°C for 2-4 hours to form an organic-inorganic hybrid silica sol. The volume ratio of methyl triethoxysilane, polyethylene glycol, ethanol, and hydrochloric acid is (1-3): (0.5-1.5): (5-10): (0.1-0.3). Maintaining 50-70°C and humidity ≤50%, 0.5-2.0% of the volume of aminopropyl triethoxysilane is added to the organic-inorganic hybrid silica sol, and the reaction is carried out for 1-2 hours to form an organic-inorganic hybrid silica gel. The organic-inorganic hybrid silica gel is placed in a drying oven, dried at 40-60° C. for 24-36 hours, and then ground and filtered using a 100-200 mesh sieve to obtain an organic-inorganic hybrid silicone resin.
[0012] Furthermore, a low-emissivity coated glass is processed by the following process, which specifically includes the following steps:
[0013] S1. Clean the glass substrate with deionized water and an ultrasonic cleaner, then wipe it with anhydrous ethanol and dry it in a drying oven for later use;
[0014] S2, mixing the polyether-modified silicone oil, acrylic resin, nano-titanium dioxide and isocyanate in the raw materials of the adhesion-promoting layer, stirring evenly to obtain a mixed solution I, using a spin coater to evenly coat the mixed solution I on the glass substrate, and then placing the coated glass substrate in an oven for drying and curing to obtain an adhesion-promoting layer;
[0015] S3, in a nitrogen atmosphere, using a magnetron sputtering coating machine, sputtering a silver target onto the adhesion promoting layer, and then placing it in a plasma treatment device, using a nitrogen, carbon tetrafluoride plasma mixed gas to plasma bombard the surface of the silver layer to obtain a plasma modified silver layer;
[0016] S4, adding ZIF-8, polyacrylic acid, sodium hexametaphosphate and fluorocarbon leveling agent in the raw materials of ZIF-8 / polyacrylic acid hybrid protective layer into deionized water, stirring evenly to obtain mixed solution II, using a spin coater to evenly coat the mixed solution II on the plasma-modified silver layer, and then placing it in an oven for drying and curing to obtain a ZIF-8 / polyacrylic acid hybrid protective layer;
[0017] S5. Add the fluorinated hyperbranched polymer, nano-cerium oxide, organic-inorganic hybrid silicone resin and hindered amine light stabilizer Tinuvin 770 in the hydrophobic antioxidant raw material layer to isopropanol and stir evenly to obtain a mixed solution III. Use a spin coater to evenly coat the mixed solution III on the ZIF-8 / polyacrylic acid hybrid protective layer, and then place it in an oven for drying and curing to obtain the ZIF-8 / polyacrylic acid hybrid protective layer.
[0018] Furthermore, in S1, the drying temperature is 80-120°C and the drying time is 30-40min, in S2, the stirring speed is 200-400r / min and the stirring time is 10-30min, the spin coating speed is 1000-3000r / min and the spin coating time is 20-40s, the drying temperature is 80-120°C and the drying time is 30-60min; in S3, the sputtering power is 100-300W and the sputtering pressure is 4-10Pa, the nitrogen flow rate in the plasma mixed gas is 15-25sccm, the carbon tetrafluoride flow rate is 8-12sccm, and the pressure is is 0.4-0.6Pa; in S4, the stirring speed is 200-400r / min, the stirring time is 10-30min, the spin coating speed is 1000-3000r / min, the spin coating time is 30-50s, the drying temperature is 100-150℃, and the drying time is 50-70min; in S5, the stirring speed is 200-400r / min, the stirring time is 10-30min, the spin coating speed is 1000-3000r / min, the spin coating time is 20-30s, the drying temperature is 80-120℃, and the drying time is 30-45min.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The present invention modifies the silver layer by using a plasma mixed gas. The high-energy particles in the plasma mixed gas collide with the surface of the silver layer, causing the electronic structure of the surface of the silver atoms to change. At the same time, the fluorine free radicals in the plasma mixed gas react chemically with the silver atoms to form a layer of silver fluoride, which can effectively isolate oxygen and water vapor from direct contact with the silver layer, thereby slowing down the oxidation process of the silver layer.
[0021] 2. The fluorine-containing hyperbranched polymer in the hydrophobic anti-oxidation layer of the present invention usually has a helical distribution of fluorine-carbon chains along the polymer chain. This arrangement allows the fluorine atoms to tightly wrap the carbon chain to form a layer of negative charge protection. This structure makes it difficult for water molecules and other polar molecules to approach the polymer surface, thereby enhancing its hydrophobic properties and effectively blocking the penetration of water molecules, thereby slowing down the oxidation process of the silver layer.
[0022] 3. The present invention can fill the tiny defects and unevenness on the surface of the glass substrate by spin coating the adhesion promotion layer on the glass substrate, thereby improving the surface flatness. At the same time, its good wettability and spreadability enable the silver layer to better contact with the glass substrate, reduce the gaps and defects between the contact surfaces, and help form a continuous and uniform silver layer, thereby improving the overall performance of the low-emissivity glass. DETAILED DESCRIPTION
[0023] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0024] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0025] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0026] Example 1
[0027] A low-emissivity coated glass comprises a glass substrate and an adhesion promoting layer, a plasma modified silver layer, a ZIF-8 / polyacrylic acid hybrid protective layer, and a hydrophobic anti-oxidation layer sequentially arranged on the glass substrate, wherein the adhesion promoting layer has a thickness of 50 nm, the plasma modified silver layer has a thickness of 20 nm, the ZIF-8 / polyacrylic acid hybrid protective layer has a thickness of 100 nm, and the hydrophobic anti-oxidation layer has a thickness of 50 nm. The raw materials of the adhesion promotion layer are composed of polyether modified silicone oil, acrylic resin, nano titanium dioxide and isocyanate with a mass volume ratio of g / mL of 1:3:0.2:0.5; the raw materials of the ZIF-8 / polyacrylic acid hybrid protective layer are composed of ZIF-8, polyacrylic acid, sodium hexametaphosphate, fluorocarbon leveling agent and deionized water with a mass volume ratio of g / mL of 3:4:0.2:0.1:20; the raw materials of the hydrophobic antioxidant layer are composed of fluorinated hyperbranched polymer, nano cerium oxide, organic-inorganic hybrid silicone resin, hindered amine light stabilizer Tinuvin 770 and isopropanol with a mass volume ratio of g / mL of 2:1:2-4:0.5:20.
[0028] The fluorine-containing hyperbranched polymer is prepared by the following method: perfluorooctyl ethyl acrylate, benzoyl peroxide, and dodecyl mercaptan are added to tetrahydrofuran, stirred at 200r / min for 60min, and a reaction mixture is obtained. The mass volume ratio of perfluorooctyl ethyl acrylate, benzoyl peroxide, dodecyl mercaptan, and tetrahydrofuran is 5:0.1:0.05:2 g / mL. Under a nitrogen atmosphere, the reaction mixture is heated to 60-80°C for reaction, and stirred at 200r / min during the reaction, and the reaction is reacted for 10h to obtain a reaction product. The reaction product is cooled to room temperature, then placed in a vacuum distillation apparatus, distilled under a vacuum degree of 30mba and a temperature of 40°C, and the distillation is stopped when the solvent in the receiving bottle no longer increases to obtain a solid substance, and the solid substance is washed twice with ethanol, and then the solid substance is placed in a drying oven at 40°C for 20h to obtain a fluorine-containing hyperbranched polymer.
[0029] The organic-inorganic hybrid silicone resin is prepared by the following method: methyltriethoxysilane and polyethylene glycol are added to ethanol, stirred at 100r / min for 30min, and then hydrochloric acid is added under stirring conditions of 200r / min, and reacted at 50°C for 4h to form an organic-inorganic hybrid silica sol. The volume ratio of methyltriethoxysilane, polyethylene glycol, ethanol, and hydrochloric acid is 1:0.5:5:0.1. Maintaining 50°C and 50% humidity, 0.5% of the volume of aminopropyltriethoxysilane is added to the organic-inorganic hybrid silica sol, and the reaction is carried out for 2h to form an organic-inorganic hybrid silica gel. The organic-inorganic hybrid silica gel is placed in a drying oven, dried at 40°C for 36h, and then ground and filtered using a 100-mesh screen to obtain an organic-inorganic hybrid silicone resin.
[0030] Example 2
[0031] A low-emissivity coated glass comprises a glass substrate and an adhesion promoting layer, a plasma modified silver layer, a ZIF-8 / polyacrylic acid hybrid protective layer, and a hydrophobic anti-oxidation layer sequentially arranged on the glass substrate, wherein the adhesion promoting layer has a thickness of 150 nm, the plasma modified silver layer has a thickness of 50 nm, the ZIF-8 / polyacrylic acid hybrid protective layer has a thickness of 200 nm, and the hydrophobic anti-oxidation layer has a thickness of 100 nm. Among them, the raw materials of the adhesion promotion layer are composed of polyether modified silicone oil, acrylic resin, nano titanium dioxide, and isocyanate with a mass volume ratio of 3:5:0.6:1.0 g / mL; the raw materials of the ZIF-8 / polyacrylic acid hybrid protective layer are composed of ZIF-8, polyacrylic acid, sodium hexametaphosphate, fluorocarbon leveling agent, and deionized water with a mass volume ratio of 3:4:0.2:0.1:20 g / mL; the raw materials of the hydrophobic antioxidant layer are composed of fluorinated hyperbranched polymer, nano cerium oxide, organic-inorganic hybrid silicone resin, hindered amine light stabilizer Tinuvin 770, and isopropyl alcohol with a mass volume ratio of 4:3:4:1.5:30 g / mL.
[0032] The fluorine-containing hyperbranched polymer is prepared by the following method: perfluorooctyl ethyl acrylate, benzoyl peroxide, and dodecyl mercaptan are added to tetrahydrofuran, stirred at 400r / min for 30min, and a reaction mixture is obtained. The mass volume ratio of perfluorooctyl ethyl acrylate, benzoyl peroxide, dodecyl mercaptan, and tetrahydrofuran is 7:0.3:0.2:4 g / mL. Under a nitrogen atmosphere, the reaction mixture is heated to 80°C for reaction, and stirred at 400r / min during the reaction, and the reaction is carried out for 6h to obtain a reaction product. The reaction product is cooled to room temperature, and then placed in a vacuum distillation apparatus, and distilled under the conditions of a vacuum degree of 50mba and a temperature of 50°C, and the distillation is stopped when the solvent in the receiving bottle no longer increases, to obtain a solid substance, and the solid substance is washed 3 times with ethanol, and then the solid substance is placed in a drying oven at 60°C for 12h to obtain a fluorine-containing hyperbranched polymer.
[0033] The organic-inorganic hybrid silicone resin is prepared by the following method: methyltriethoxysilane and polyethylene glycol are added to ethanol, stirred at 300r / min for 10min, and then hydrochloric acid is added under stirring conditions of 300r / min, and reacted at 70°C for 2h to form an organic-inorganic hybrid silica sol. The volume ratio of methyltriethoxysilane, polyethylene glycol, ethanol, and hydrochloric acid is 3:1.5:10:0.3. Maintaining 70°C and humidity of 40%, 2.0% of the volume of aminopropyltriethoxysilane is added to the organic-inorganic hybrid silica sol, and the reaction is carried out for 1h to form an organic-inorganic hybrid silica gel. The organic-inorganic hybrid silica gel is placed in a drying oven, dried at 60°C for 24h, and then ground and filtered using a 200-mesh screen to obtain an organic-inorganic hybrid silicone resin.
[0034] Example 3
[0035] A low-emissivity coated glass comprises a glass substrate and an adhesion promoting layer, a plasma modified silver layer, a ZIF-8 / polyacrylic acid hybrid protective layer, and a hydrophobic anti-oxidation layer sequentially arranged on the glass substrate, wherein the adhesion promoting layer has a thickness of 100 nm, the plasma modified silver layer has a thickness of 35 nm, the ZIF-8 / polyacrylic acid hybrid protective layer has a thickness of 150 nm, and the hydrophobic anti-oxidation layer has a thickness of 75 nm. Among them, the raw materials of the adhesion promotion layer are composed of polyether modified silicone oil, acrylic resin, nano titanium dioxide, and isocyanate with a mass volume ratio of 2:4:0.4:0.7 g / mL; the raw materials of the ZIF-8 / polyacrylic acid hybrid protective layer are composed of ZIF-8, polyacrylic acid, sodium hexametaphosphate, fluorocarbon leveling agent, and deionized water with a mass volume ratio of 4:6:0.3:0.2:30 g / mL; the raw materials of the hydrophobic antioxidant layer are composed of fluorinated hyperbranched polymer, nano cerium oxide, organic-inorganic hybrid silicone resin, hindered amine light stabilizer Tinuvin 770, and isopropyl alcohol with a mass volume ratio of 3:2:3:1:25 g / mL.
[0036] The fluorine-containing hyperbranched polymer is prepared by the following method: adding perfluorooctyl ethyl acrylate, benzoyl peroxide, and dodecyl mercaptan to tetrahydrofuran, stirring at 300r / min for 45min, and obtaining a reaction mixture. The mass volume ratio of perfluorooctyl ethyl acrylate, benzoyl peroxide, dodecyl mercaptan, and tetrahydrofuran is 6:0.2:0.13:3 g / mL. Under a nitrogen atmosphere, the reaction mixture is heated to 70°C for reaction, and stirring is maintained at 300r / min during the reaction process, and the reaction is performed for 8h to obtain a reaction product. The reaction product is cooled to room temperature, and then placed in a vacuum distillation apparatus, and distilled under a vacuum degree of 40mba and a temperature of 45°C. The distillation is stopped when the solvent in the receiving bottle no longer increases, and a solid substance is obtained. The solid substance is washed 3 times with ethanol, and then the solid substance is placed in a drying oven at 50°C for 16h to obtain a fluorine-containing hyperbranched polymer.
[0037] The organic-inorganic hybrid silicone resin is prepared by the following method: methyltriethoxysilane and polyethylene glycol are added to ethanol, stirred at 200r / min for 20min, and then hydrochloric acid is added under stirring conditions of 250r / min, and reacted at 60°C for 3h to form an organic-inorganic hybrid silica sol. The volume ratio of methyltriethoxysilane, polyethylene glycol, ethanol, and hydrochloric acid is 2:1:7.5:0.2. Maintaining 60°C and humidity of 45%, 1.3% of aminopropyltriethoxysilane by volume is added to the organic-inorganic hybrid silica sol, and the reaction is carried out for 1.5h to form an organic-inorganic hybrid silica gel. The organic-inorganic hybrid silica gel is placed in a drying oven, dried at 50°C for 30h, and then ground and filtered using a 150-mesh screen to obtain an organic-inorganic hybrid silicone resin.
[0038] The low-emissivity coated glass described in the above embodiments 1-3 is processed by the following process, which specifically includes the following steps:
[0039] S1. Clean the glass substrate with deionized water and an ultrasonic cleaner, then wipe it with anhydrous ethanol and dry it in a drying oven at 100° C. for 35 min for later use;
[0040] S2, the polyether modified silicone oil, acrylic resin, nano titanium dioxide and isocyanate in the raw materials of the adhesion promotion layer are mixed, stirred at a speed of 300 r / min for 20 min to obtain a mixed solution I, and the mixed solution I is evenly coated on the glass substrate by spin coating at a speed of 2000 r / min for 30 s using a spin coater, and then the coated glass substrate is placed in an oven at 100° C. for drying and curing, and dried for 45 min to obtain an adhesion promotion layer;
[0041] S3. In a nitrogen atmosphere, a magnetron sputtering coating machine is used to sputter a silver target onto the adhesion promoting layer at a sputtering power of 200 W and a sputtering pressure of 7 Pa, and then the target is placed in a plasma treatment device, and a plasma mixed gas of nitrogen and carbon tetrafluoride is used to perform plasma bombardment on the surface of the silver layer to obtain a plasma-modified silver layer; the nitrogen flow rate in the plasma mixed gas is 20 sccm, the carbon tetrafluoride flow rate is 10 sccm, and the pressure is 0.5 Pa;
[0042] S4, adding ZIF-8, polyacrylic acid, sodium hexametaphosphate and fluorocarbon leveling agent in the raw materials of ZIF-8 / polyacrylic acid hybrid protective layer into deionized water, stirring at a speed of 300 r / min for 20 min to obtain mixed solution II, using a spin coater to spin coat at a speed of 2000 r / min for 45 s to evenly coat the mixed solution II on the plasma-modified silver layer, and then placing in an oven to dry and solidify at 125° C., and drying for 60 min to obtain a ZIF-8 / polyacrylic acid hybrid protective layer;
[0043] S5. Add the fluorinated hyperbranched polymer, nano-cerium oxide, organic-inorganic hybrid silicone resin and hindered amine light stabilizer Tinuvin 770 in the raw materials of the hydrophobic antioxidant layer to isopropanol, stir at a speed of 300 r / min for 20 min to obtain a mixed solution III, use a spin coater to spin coat the mixed solution III at a speed of 2000 r / min for 25 s to evenly coat the ZIF-8 / polyacrylic acid hybrid protective layer, and then place it in an oven at 100°C for drying and curing, and dry it for 38 min to obtain a ZIF-8 / polyacrylic acid hybrid protective layer.
[0044] Example 4
[0045] Compared with Example 3, this embodiment is different in that the low-emissivity coated glass is processed by the following process, which specifically includes the following steps:
[0046] S1. Clean the glass substrate with deionized water and an ultrasonic cleaner, then wipe it with anhydrous ethanol and dry it in a drying oven at 80° C. for 40 min for later use;
[0047] S2, the polyether modified silicone oil, acrylic resin, nano titanium dioxide and isocyanate in the raw materials of the adhesion promotion layer are mixed, stirred at a speed of 200 r / min for 30 min to obtain a mixed solution I, and the mixed solution I is evenly coated on the glass substrate by using a spin coater at a speed of 1000 r / min for 40 s, and then the coated glass substrate is placed in an oven at 80° C. for drying and curing, and dried for 60 min to obtain an adhesion promotion layer;
[0048] S3. In a nitrogen atmosphere, a magnetron sputtering coating machine is used to sputter a silver target onto the adhesion promoting layer at a sputtering power of 100 W and a sputtering pressure of 4 Pa, and then the target is placed in a plasma treatment device, and a plasma bombardment is performed on the surface of the silver layer using a nitrogen and carbon tetrafluoride plasma mixed gas to obtain a plasma-modified silver layer; the nitrogen flow rate in the plasma mixed gas is 15 sccm, the carbon tetrafluoride flow rate is 8 sccm, and the pressure is 0.4 Pa;
[0049] S4, adding ZIF-8, polyacrylic acid, sodium hexametaphosphate and fluorocarbon leveling agent in the raw materials of ZIF-8 / polyacrylic acid hybrid protective layer into deionized water, stirring at a speed of 200 r / min for 30 min to obtain mixed solution II, using a spin coater to spin coat at a speed of 1000 r / min for 50 s to evenly coat the mixed solution II on the plasma-modified silver layer, and then placing it in an oven at 100° C. for drying and curing, and drying for 70 min to obtain a ZIF-8 / polyacrylic acid hybrid protective layer;
[0050] S5. Add the fluorinated hyperbranched polymer, nano-cerium oxide, organic-inorganic hybrid silicone resin and hindered amine light stabilizer Tinuvin 770 in the raw materials of the hydrophobic antioxidant layer to isopropanol, stir at a speed of 200 r / min for 30 minutes to obtain a mixed solution III, use a spin coater to spin coat the mixed solution III at a speed of 1000 r / min for 20 seconds to evenly coat the ZIF-8 / polyacrylic acid hybrid protective layer, and then place it in an oven for drying and curing at 80°C for 45 minutes to obtain a ZIF-8 / polyacrylic acid hybrid protective layer.
[0051] Example 5
[0052] Compared with Example 3, this embodiment is different in that the low-emissivity coated glass is processed by the following process, which specifically includes the following steps:
[0053] S1. Clean the glass substrate with deionized water and an ultrasonic cleaner, then wipe it with anhydrous ethanol and dry it in a drying oven at 120° C. for 30 min for later use;
[0054] S2, the polyether modified silicone oil, acrylic resin, nano titanium dioxide and isocyanate in the raw materials of the adhesion promotion layer are mixed, stirred at a speed of 400 r / min for 10 min to obtain a mixed solution I, and the mixed solution I is evenly coated on the glass substrate by spin coating at a speed of 3000 r / min for 20, and then the coated glass substrate is placed in an oven at 120° C. for drying and curing, and dried for 30 min to obtain an adhesion promotion layer;
[0055] S3. In a nitrogen atmosphere, a magnetron sputtering coating machine is used to sputter a silver target onto the adhesion promoting layer at a sputtering power of 300 W and a sputtering pressure of 10 Pa, and then the target is placed in a plasma treatment device, and a plasma mixed gas of nitrogen and carbon tetrafluoride is used to plasma bombard the surface of the silver layer to obtain a plasma-modified silver layer; the nitrogen flow rate in the plasma mixed gas is 25 sccm, the carbon tetrafluoride flow rate is 12 sccm, and the pressure is 0.4-0.6 Pa;
[0056] S4, adding ZIF-8, polyacrylic acid, sodium hexametaphosphate and fluorocarbon leveling agent in the raw materials of ZIF-8 / polyacrylic acid hybrid protective layer into deionized water, stirring at a speed of 400 r / min for 30 min to obtain mixed solution II, using a spin coater to spin coat at a speed of 3000 r / min for 30 s to evenly coat the mixed solution II on the plasma-modified silver layer, and then placing it in an oven for drying and curing at 150° C., and drying for 50 min to obtain a ZIF-8 / polyacrylic acid hybrid protective layer;
[0057] S5. Add the fluorinated hyperbranched polymer, nano-cerium oxide, organic-inorganic hybrid silicone resin and hindered amine light stabilizer Tinuvin 770 in the raw materials of the hydrophobic antioxidant layer to isopropanol, stir at a speed of 400 r / min for 10 min to obtain a mixed solution III, use a spin coater to spin coat the mixed solution III at a speed of 3000 r / min for 20 s to evenly coat the ZIF-8 / polyacrylic acid hybrid protective layer, and then place it in an oven for drying and curing at 120°C for 30 min to obtain a ZIF-8 / polyacrylic acid hybrid protective layer.
[0058] Comparative Example 1
[0059] The difference between this comparative example and Example 3 is that the silver layer is not modified, that is, the silver target is sputtered onto the adhesion promoting layer under the conditions of a sputtering power of 300 W and a sputtering gas pressure of 10 Pa.
[0060] Comparative Example 2
[0061] This comparative example is compared with Example 3, except that the ZIF-8 / polyacrylic acid hybrid protective layer raw material does not contain ZIF-8, that is, the ZIF-8 / polyacrylic acid hybrid protective layer raw material consists of polyacrylic acid, sodium hexametaphosphate, fluorocarbon leveling agent, and deionized water in a mass volume ratio of 6:0.3:0.2:30 g / mL.
[0062] Comparative Example 3
[0063] Compared with Example 3, the difference between this comparative example is that the hydrophobic antioxidant layer raw material does not contain a fluorine-containing hyperbranched polymer, that is, the hydrophobic antioxidant layer raw material consists of nano-cerium oxide, organic-inorganic hybrid silicone resin, hindered amine light stabilizer Tinuvin 770, and isopropanol in a mass volume ratio of g / mL of 2:3:1:25.
[0064] Comparative Example 4
[0065] Compared with Example 3, the difference between this comparative example and Example 3 is that the hydrophobic antioxidant layer raw material does not contain organic-inorganic hybrid silicone resin, that is, the hydrophobic antioxidant layer raw material consists of a fluorine-containing hyperbranched polymer, nano cerium oxide, hindered amine light stabilizer Tinuvin 770, and isopropanol in a mass volume ratio of g / mL of 3:2:1:25.
[0066] Comparative Example 5
[0067] The difference between this comparative example and Example 3 is that the low-emissivity coated glass does not contain an adhesion promoting layer.
[0068] 1. Antioxidant performance test
[0069] The low-emissivity coated glass obtained in Examples 1-5 and Comparative Examples 1-4 were cut into 30 mm × 50 mm sizes, and then placed in a damp heat aging test chamber for 1000 hours at 60°C and 90% humidity. After the test, the glass surface was observed for oxidation spots and discoloration, and the results are shown in Table 1.
[0070] Table 1
[0071] Are there any oxidation spots? Whether to change color Example 1 No oxidation spots No color change Example 2 No oxidation spots No color change Example 3 No oxidation spots No color change Example 4 No oxidation spots No color change Example 5 No oxidation spots No color change Comparative Example 1 More obvious oxidation spots Slightly darkened Comparative Example 2 A few fine oxidation spots No color change Comparative Example 3 A few fine oxidation spots No color change Comparative Example 4 A few fine oxidation spots No color change
[0072] It can be seen from Table 1 that the low-emissivity coated glass prepared in Examples 1-5 has better anti-oxidation performance than that in Comparative Examples 1-4.
[0073] The plasma modified silver layer in the embodiment 1-5 has high energy particles in the plasma mixed gas during the modification process, such as electrons, ions and free radicals collide with the silver layer surface, causing the electronic structure of the silver atom surface to change, and the fluorine free radicals in the plasma mixed gas react chemically with the silver atoms to form a layer of silver fluoride, which has high chemical stability and can effectively isolate the direct contact of oxygen and water vapor with the silver layer, thereby slowing down the oxidation process of the silver layer. And plasma bombardment can also change the morphology and structure of the silver layer surface, making it more compact and flat, thereby reducing the adsorption and penetration of oxygen and water vapor on the silver layer surface, and further improving the anti-oxidation performance of the silver layer. Therefore, the silver layer is modified by the plasma mixed gas, and its anti-oxidation performance has been greatly improved.
[0074] ZIF-8 / polyacrylic acid hybrid protective layer in embodiment 1-5 wherein ZIF-8 has a high porosity and specific surface area, and its pore structure can effectively capture and isolate oxygen and water vapor in the environment, preventing them from directly contacting the plasma modified silver layer. In addition, the chemical stability of ZIF-8 also ensures that it can maintain the integrity of the structure during long-term use, and continuously plays a barrier role. Polyacrylic acid wherein can be closely combined with ZIF-8 particles to form a uniform hybrid coating. This combination not only enhances the mechanical strength of the coating, but also improves the compactness of the coating. The adhesion of polyacrylic acid ensures that the coating can be firmly attached to the plasma modified silver layer, and is not easy to fall off or peel off. At the same time, polyacrylic acid can also provide certain flexibility for the coating, so that it can better adapt to the deformation of the substrate, and reduce the coating rupture caused by stress concentration. Sodium hexametaphosphate wherein can help ZIF-8 particles to be evenly dispersed in polyacrylic acid, prevent particles from agglomerating, and the addition of fluorocarbon leveling agent enables ZIF-8 / polyacrylic acid hybrid protective layer to form a more uniform and smooth coating during spin coating. The synergistic effect between these raw materials enables the ZIF-8 / polyacrylic acid hybrid protective layer to effectively block the contact of oxygen and water vapor with the plasma-modified silver layer, thereby further improving the antioxidant performance of the silver layer.
[0075] The fluorine-containing hyperbranched polymer in the hydrophobic anti-oxidation layer in Examples 1-5 is usually spirally distributed along the polymer chain. This arrangement allows the fluorine atoms to tightly wrap the carbon chain to form a layer of negative charge protection. This structure makes it difficult for water molecules and other polar molecules to approach the polymer surface, thereby enhancing its hydrophobic properties, effectively blocking the penetration of water molecules, and thus slowing down the oxidation process of the silver layer. The nano-cerium oxide therein can effectively absorb and disperse ultraviolet rays, reduce the damage of ultraviolet rays to the hydrophobic anti-oxidation layer, and has a certain catalytic effect, can decompose some harmful substances, and keep the hydrophobic anti-oxidation layer clean and stable. Tinuvin 770 therein can absorb and disperse ultraviolet rays, prevent ultraviolet rays from damaging the coating, and also has an antioxidant effect, which can inhibit the generation and propagation of free radicals in the coating. Tinuvin 770 works together with nano-cerium oxide to enhance the anti-ultraviolet and anti-oxidation properties of the coating. They work together to form a multiple protection mechanism, effectively extending the service life of the hydrophobic anti-oxidation layer. The organic-inorganic hybrid silicone resin combines the flexibility of organic polymers with the hardness and weather resistance of inorganic materials, has good film-forming properties and adhesion, and can form a dense coating to effectively block the erosion of the external environment. Therefore, the hydrophobic and anti-oxidation layer formed by the close combination of organic-inorganic hybrid silicone resin, fluorine-containing hyperbranched polymer, nano-cerium oxide, and Tinuvin 770 has excellent hydrophobic and anti-oxidation properties.
[0076] 2. Test of bonding strength between film layer and glass substrate
[0077] The low-emissivity coated glasses prepared in Examples 1-5 and Comparative Example 5 were respectively cut into 25 mm × 50 mm sizes as test pieces, and then the test pieces were fixed on a test bench. A scratch tester equipped with a diamond scratch needle was used to apply gradually increasing force to the coating layer to perform continuous scratches. The load force required when the film layer was obviously peeled off was monitored and recorded. The results are shown in Table 2.
[0078] Table 2
[0079] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 5 Load force / N 38.1 37.9 39.2 38.3 37.5 29.8
[0080] As can be seen from Table 2, compared with Comparative Example 5, the bonding force of the film layer and the glass substrate of Example 1-5 is stronger. This is because, in Example 1-5, by first spin coating the adhesion promotion layer on the glass substrate, the polyether-modified silicone oil therein can form a uniform film on the surface of the glass substrate, effectively improve the wettability of the substrate surface, so that the subsequent coating material can be better attached to the substrate, and the acrylic resin therein has good adhesion and film-forming properties and can form a strong chemical bond with the surface of the glass substrate, improve the bonding strength of the film layer and the substrate, and the nano titanium dioxide therein can play a role of filling and strengthening, improve the mechanical strength and wear resistance of the adhesion promotion layer. Titanium dioxide can also react chemically with the active groups such as hydroxyl groups on the surface of the glass substrate to form chemical bonding, thereby further enhancing the bonding force of the film layer and the substrate. Isocyanate therein can react cross-linking with the functional groups such as hydroxyl groups in the acrylic resin, forming a dense cross-linked network structure to significantly improve the cohesion and adhesion of the adhesion promotion layer, so that the film layer is more firmly attached to the glass substrate. By spin coating the adhesion-promoting layer on the glass substrate, the tiny defects and unevenness on the surface of the glass substrate can be filled, and the surface flatness can be improved. At the same time, its good wettability and spreading properties enable the silver layer to better contact with the glass substrate, reduce the gaps and defects between the contact surfaces, and help form a continuous and uniform silver layer, thereby improving the overall performance of the low-e glass.
[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A low-emissivity coated glass, characterized in that: The invention comprises a glass substrate and an adhesion promoting layer, a plasma modified silver layer, a ZIF-8 / polyacrylic acid hybrid protective layer and a hydrophobic anti-oxidation layer which are sequentially arranged on the glass substrate.
2. The low-emissivity coated glass according to claim 1, characterized in that: The thickness of the adhesion promotion layer is 50-150nm, the thickness of the plasma modified silver layer is 20-50nm, the thickness of the ZIF-8 / polyacrylic acid hybrid protective layer is 100-200nm, and the thickness of the hydrophobic anti-oxidation layer is 50-100nm.
3. The low-emissivity coated glass according to claim 1, characterized in that: The raw materials of the adhesion promotion layer are composed of polyether modified silicone oil, acrylic resin, nano titanium dioxide and isocyanate in a mass volume ratio of (1-3):(3-5):(0.2-0.6):(0.5-1.0) g / mL.
4. The low-emissivity coated glass according to claim 1, characterized in that: The ZIF-8 / polyacrylic acid hybrid protective layer raw materials are composed of ZIF-8, polyacrylic acid, sodium hexametaphosphate, fluorocarbon leveling agent and deionized water in a mass volume ratio of g / mL of (3-5):(4-8):(0.2-0.5):(0.1-0.3):(20-40).
5. The low-emissivity coated glass according to claim 1, characterized in that: The hydrophobic anti-oxidation layer raw materials are composed of fluorine-containing hyperbranched polymer, nano cerium oxide, organic-inorganic hybrid silicone resin, hindered amine light stabilizer Tinuvin 770 and isopropyl alcohol with a mass volume ratio of g / mL of (2-4):(1-3):(2-4):(0.5-1.5):(20-30).
6. The low-emissivity coated glass according to claim 5, characterized in that: The fluorine-containing hyperbranched polymer is prepared by the following method: adding perfluorooctyl ethyl acrylate, benzoyl peroxide, and dodecyl mercaptan to tetrahydrofuran, stirring at 200-400 r / min for 30-60 min to obtain a reaction mixture, wherein the mass volume ratio of the perfluorooctyl ethyl acrylate, benzoyl peroxide, dodecyl mercaptan, and tetrahydrofuran is (5-7) g / mL: (0.1-0.3) g / mL: (0.05-0.2) g / mL: (2-4) under a nitrogen atmosphere, heating the reaction mixture to 60-80 ℃, stirring at 200-400r / min during the reaction, reacting for 6-10h to obtain a reaction product; cooling the reaction product to room temperature, then placing it in a vacuum distillation device, distilling it under the conditions of a vacuum degree of 30-50mba and a temperature of 40-50℃, stopping the distillation when the solvent in the receiving bottle no longer increases, obtaining a solid substance, washing the solid substance with ethanol for 2-3 times, and then placing the solid substance in a drying oven at 40-60℃ to dry it for 12-20h to obtain a fluorine-containing hyperbranched polymer.
7. The low-emissivity coated glass according to claim 5, characterized in that: The organic-inorganic hybrid silicone resin is prepared by the following method: methyltriethoxysilane and polyethylene glycol are added to ethanol, stirred at 100-300 r / min for 10-30 min, and then hydrochloric acid is added under stirring conditions of 200-300 r / min, and reacted at 50-70° C. for 2-4 h to form an organic-inorganic hybrid silica sol, wherein the volume ratio of methyltriethoxysilane, polyethylene glycol, ethanol, and hydrochloric acid is (1-3):(0.5-1.5):( 5-10):(0.1-0.3); maintaining 50-70°C and humidity ≤50%, adding 0.5-2.0% of its volume of aminopropyltriethoxysilane to the organic-inorganic hybrid silica sol, reacting for 1-2h to form an organic-inorganic hybrid silica gel; placing the organic-inorganic hybrid silica gel in a drying oven, drying it at 40-60°C for 24-36h, then grinding it and filtering it through a 100-200 mesh sieve to obtain an organic-inorganic hybrid silicone resin.
8. A processing technology for low-emissivity coated glass according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Clean the glass substrate with deionized water and an ultrasonic cleaner, then wipe it with anhydrous ethanol and dry it in a drying oven for later use; S2, mixing the polyether-modified silicone oil, acrylic resin, nano-titanium dioxide and isocyanate in the raw materials of the adhesion-promoting layer, stirring evenly to obtain a mixed solution I, using a spin coater to evenly coat the mixed solution I on the glass substrate, and then placing the coated glass substrate in an oven for drying and curing to obtain an adhesion-promoting layer; S3, in a nitrogen atmosphere, using a magnetron sputtering coating machine, sputtering a silver target onto the adhesion promoting layer, and then placing it in a plasma treatment device, using a nitrogen, carbon tetrafluoride plasma mixed gas to plasma bombard the surface of the silver layer to obtain a plasma modified silver layer; S4, adding ZIF-8, polyacrylic acid, sodium hexametaphosphate and fluorocarbon leveling agent in the raw materials of ZIF-8 / polyacrylic acid hybrid protective layer into deionized water, stirring evenly to obtain mixed solution II, using a spin coater to evenly coat the mixed solution II on the plasma-modified silver layer, and then placing it in an oven for drying and curing to obtain a ZIF-8 / polyacrylic acid hybrid protective layer; S5. Add the fluorinated hyperbranched polymer, nano-cerium oxide, organic-inorganic hybrid silicone resin and hindered amine light stabilizer Tinuvin 770 in the hydrophobic antioxidant raw materials to isopropanol and stir evenly to obtain a mixed solution III. Use a spin coater to evenly coat the mixed solution III on the ZIF-8 / polyacrylic acid hybrid protective layer, and then place it in an oven for drying and curing to obtain a ZIF-8 / polyacrylic acid hybrid protective layer.
9. The processing technology of low-emissivity coated glass according to claim 8, characterized in that: In the S1, the drying temperature is 80-120°C and the drying time is 30-40min. In the S2, the stirring speed is 200-400r / min and the stirring time is 10-30min. The spin coating speed is 1000-3000r / min and the spin coating time is 20-40s. The drying temperature is 80-120°C and the drying time is 30-60min. In the S3, the sputtering power is 100-300W and the sputtering pressure is 4-10Pa. The nitrogen flow rate in the plasma mixed gas is 15-25sccm, the carbon tetrafluoride flow rate is 8-12sccm, and the pressure is 0 .4-0.6Pa; in S4, the stirring speed is 200-400r / min, the stirring time is 10-30min, the spin coating speed is 1000-3000r / min, the spin coating time is 30-50s, the drying temperature is 100-150℃, and the drying time is 50-70min; in S5, the stirring speed is 200-400r / min, the stirring time is 10-30min, the spin coating speed is 1000-3000r / min, the spin coating time is 20-30s, the drying temperature is 80-120℃, and the drying time is 30-45min.